Effet de l’incorporation des additifs naturels sur la qualité de la viande de poulet de Chair - BACHA, Hadil; BERRADIA, Nabila (My University, 2023)
Faced with the challenges of the poultry industry and the growing demand for quality chicken meat, how can the incorporation of turmeric essential oil and pomegranate bark powder in broiler feed influence their zootechnical performance, the nutritional quality of their meat, and even their health? For these reasons, our study was designed to assess the impact of turmeric essential oil and pomegranate bark powder on broiler feed (ARBOR ACRES strain). We examined their effects on zootechnical parameters and meat nutritional quality. The experiment took place at the MAZAGRAN breeding facility, in the wilaya of MOSTAGANEM. Daily monitoring of the farm, including visits and daily reports, enabled the collection of information and observations relating to zootechnical parameters. In addition, physico-chemical analyses of the meat were carried out in the applied animal physiology laboratory. Our results indicate that the use of pomegranate bark powder has no significant effect on the growth performance of broilers, nor on the nutritional quality of their meat. Turmeric oil, on the other hand, had a positive and significant effect on average weight gain of 21.833 compared with the other two batches.
Keywords: poulet de chair; l’huile essentielle du curcuma; poudre d’écorce de grenade; viande; paramètres zootechniques